A meta-analysis to identify factors affecting solid and liquid digesta mean retention time in equines - Papadakis, K.; Leishman, E.M.; Darani, P.S.; Cieslar, S.; Ellis, J.L. (Journal of equine veterinary science, 2025)
How quickly feed passes through the equine gastrointestinal tract (GIT) or specific compartments of the GIT is an important determinant of nutrient digestion and absorption. Typically, this process is quantified by measuring mean retention time (MRT), or the average number of hours required to pass a labeled feedstuff/digesta fraction. While determinants of MRT have been studied extensively in other species resulting in empirical equations, equine data lack such quantitative summaries. The variability in experimental diets and subjects (i.e., sex, breed, age) across equine studies makes qualitative comparisons difficult. Therefore, the objective of this study was to conduct a meta-analysis across available MRT data from published equine studies to determine factors (e.g., dietary, physiological, management) that affect equine MRT and to develop predictive/descriptive equations for MRT in equines. Such equations would be useful in the prediction of feedstuff or nutrient digestibility, as well as the development of models of nutrient utilization. A systematic literature search was conducted which yielded 24 papers (144 mean observations of total-tract MRT, for solid and liquid digesta) that met the criteria for inclusion (must report MRT, and have a change in diet given). Information extracted from the papers included (as available) body weight, classification as horse or pony, age, dry matter intake, forage particle size, feed ingredients, diet nutrient composition, forage to concentrate ratio, and so on. A linear mixed model analysis treating study as a random effect was conducted to identify significant driving variables and quantify their effects on MRT across the published literature. Model fit was evaluated using visual plots, root Mean Square Prediction Error (rMSPE), and the Concordance Correlation Coefficient (CCC) statistic. For total-tract liquid digesta MRT (h), it was found that whether the equine was a horse or pony, the DMI (kg/d) and ADF (g/kg DM) content of the diet yielded the best model predictions (raw CCC: 0.712, raw rMSPE: 22.0%, conditioned CCC: 0.900, conditioned rMSPE 12.9%). For the solid digesta MRT (h) models, whether it was a horse or pony, the DMI (kg/d), the roughage percent of the diet, and the NDF (g/kg DM) content of the diet yielded the best model predictions (raw CCC: 0.469, raw rMSPE: 18.6%, conditioned CCC: 0.885, conditioned rMSPE 9.1%). These models confirm existing knowledge while developing tools to predict MRT in horses going forward, not only advancing the field of quantitative equine nutrition but also enhancing our ability to predict nutrient digestibility in horses.